PENGARUH KUALITAS PELAYANAN DAN MEDIA SOSIAL TERHADAP MINAT RELAWAN DONOR DARAH DI UNIT DONOR DARAH PMI KABUPATEN GIANYAR - Putri Anggreni; Kadek Anggi Puspita Yanti (Forum Manajemen STIMI Handayani Denpasar, 2019)
This study aims to determine and analyze how much influence the quality of service and social media to interest of blood donor volunteers at Unit Donor Darah PMI Kabupaten Gianyar. Results of data processing with SPSS For Windows Version 24 obtained the results of multiple linear regression results obtained results of multiple linear regression analysis Y = 4,982 + 0,088X1 + 0,439X2. The result of the analysis of multiple correlation is 0,730, lies between 0.60 to 0.799 which means there is a positive and strong correlation. Based on the result of determination analysis, the value of R2 stated that 55,1% of blood donor volunteer interest is influenced by both variables, service quality and social media, the rest 44,9% volunteer donor blood interest influenced by other variables outside of research. Simultaneously the quality of service and social media influence on the real interest of blood donor at Unit Donor Darah PMI Kabupaten Gianyar. Partially, the service quality (X1) and social media (X2) have positive and significant effect on interest of blood donor volunteer in Unit Donor Darah PMI Kabupaten Gianyar. Thus the quality of service and social media is not only important for the company or profit organization but for non profit organization both of them give a positive effect. Especially for Unit Donor Darah PMI Kabupaten Gianyar engaged in community services, especially blood transfusion.